Effect of enriched Artemia on the growth performance and survival of red tilapia (Oreochromis sp.) larvae - Abd. Rahim, Nuramizah (2013)
The effects of live feed (Artemia) enrichment on the growth performance and survival rate of Red Tilapia (Oreochromis sp.) larvae on the tank were studied. This project was conducted at the Institute of Bioscience, University Putra Malaysia for two weeks. Oreochromis sp. about 10 day old were stocked into different treatment tanks, each tank way filled with 10L of dechlorinated aerated tap water and 100 larvae. There were 4 different treatment tanks, each treatment consisted of 3 replicates. The tanks were randomly assigned in completely randomized design (CRD). The different treatments tested were T1 (non– Artemia enriched), T2 (Artemia enriched with Spirulina in 3 hours), T3 (Artemia enriched with Spirulina in 6 hours) and T4 (Artemia enriched with Spirulina in 9 hours). The Artemia were the frozen before fed to the larvae ad libitium three times per day. The growth performance and survival rate were conducted on 0th, 3rd, 6th, 9th, 12th and 14th. During the experimental period, water quality parameter such as dissolved oxygen, pH, ammonia and temperature were monitored. The growth performances of larvae Oreochromis sp. were determined and the data of their total weight, total lengths were collected till the end of experiment. The result showed that unenriched Artemia and enriched Artemia the significant different (P<0.05). Futhermore, also at the end of the project, larvae fish fed with T4 (Artemia enriched with Spirulina in 9 hours) gave a better performance of growth and survival compared to fish fed with treatments T1, T2 and T3.